Development of Mixed Learning Media (MLM) Assisted by Student Worksheet on The Topic of The Effect of Molarity on Light Index - Baifeto, Ekri Pranata Ferdinand; Aulia, Maghfira; Hasbi, Julia Edwina; Sundari, Resti; Rusdiana, Dadi (Indonesian Journal of Science and Mathematics Education, 2021)
The purpose of this study was to develop mixed learning media (MLM) and test the feasibility of learning media. The study was conducted using the research and development method which refers to the ADDIE model with four main steps, analysis, design, development, and implementation. The instrument used is a questionnaire consisting of a learning media questionnaire, student worksheet questionnaire, and student response questionnaire. Respondents in this study were 4 eleventh grade students. The results showed the feasibility of learning media with a score of 92.5%; in the aspect of serving by 93.3%; on the aspect of the feasibility of the content of 91.6%; on the language aspect by 91.5%; 95.8% on the concept and task aspects. Based on the results of the validation score, the student worksheet was declared very valid. Based on the results of student questionnaire data, an average score of 94.9%. The results showed that the learning media were valid and practical to use for virtual experiments.